2011
DOI: 10.1021/bi2004685
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Filament Conformation Dictate Seeding Barrier between Three- and Four-Repeat Tau

Abstract: Tau filaments are the pathological hallmark of >20 neurodegenerative diseases including Alzheimer's disease. Six tau isoforms exist that can be grouped into 4-repeat (4R) tau and 3-repeat (3R) tau based on the presence or absence of the second of four microtubule binding repeats. Recent evidence suggests that tau filaments can transfer between cells and spread through the brain. Here we demonstrate in vitro that seeded filament growth, a prerequisite for tau spreading, is crucially dependent on the isoform com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
103
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 48 publications
9
103
2
Order By: Relevance
“…The aggregates characteristic of AGD, PSP, and CBD are made of four-repeat tau, as is the human tau isoform the ALZ17 line is transgenic for. These findings agree with in vitro studies that have shown that seeds made of either three-repeat, three/four-repeat, or four-repeat tau can recruit soluble four-repeat tau (32).…”
Section: Discussionsupporting
confidence: 91%
“…The aggregates characteristic of AGD, PSP, and CBD are made of four-repeat tau, as is the human tau isoform the ALZ17 line is transgenic for. These findings agree with in vitro studies that have shown that seeds made of either three-repeat, three/four-repeat, or four-repeat tau can recruit soluble four-repeat tau (32).…”
Section: Discussionsupporting
confidence: 91%
“…Using the recombinant K18 and K19 constructs, which encode the 4R and 3R RDs of tau, respectively, Dinkel et al (47) demonstrated that heparin-induced K19 3R aggregates could not seed filaments formed from K18 4R monomers. In a separate experiment, recombinant 1N3R or 1N4R human tau fibrils were used to test the cross-isoform prion replication barrier in the neuroblastoma cell line SH-SY5Y (48).…”
Section: Discussionmentioning
confidence: 99%
“…Such a structural polymorphism has been observed in amyloids formed by proteins as varied as lysozyme, insulin, amyloid-␤, ␣-synuclein, tau, ␤ 2 -microglobulin, recombinant mammalian PrP, and the yeast prion protein Sup35 (24,35,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). However, the molecular level details giving rise to amyloid strains may vary with the constitutive protein.…”
Section: Discussionmentioning
confidence: 99%